Certain Results on Ricci Solitons in α-Sasakian Manifolds. (15th July 2013) - Ashoka, S. R.; Bagewadi, C. S.; Ingalahalli, Gurupadavva
Abstract : We study Ricci solitons in α -Sasakian manifolds and show that it is a shrinking or expanding soliton and the manifold is Einstein with Killing vector field. Further, we prove that if V is conformal Killilng vector field, then the Ricci soliton in 3-dimensional α -Sasakian manifolds is shrinking or expanding but cannot be steady.